The PaCO2-ETCO2 gradient in pre-hospital intubations of all aetiologies from a single UK helicopter emergency medicine service 2015–2018. (February 2022) - Hibberd, Owen; Hazlerigg, Antonia; Cocker, Paul John; Wilson, Alastair W; Berry, Neil; Harris, Tim
Background: Control of the arterial partial pressure of carbon dioxide (PaCO2 ) is important in the ventilated patient. End-tidal carbon dioxide (ETCO2 ) levels are often used as a proxy, but are clinically limited. The difference between the PaCO2 and ETCO2 has been suggested to be 0.5–1.0 kPa. However, this has not been consistently reflected in the physiologically unstable pre-hospital patient. This study aims to elucidate the PaCO2 -ETCO2 gradient for pre-hospital intubated patients. Methods: This was a retrospective, cohort study using data identified from the HEMSbase 2 database (Feb 2015–Nov 2018). Patients were included if they had documented ETCO2 and arterial PaCO2 measurements. Arterial PaCO2 data that could not be linked to within 5 minutes of ETCO2 were excluded. Bland-Altman plots were calculated to describe agreement. Results: A total of 73 patients were identified. Aetiology was arranged into three categories: 13 (17.8%) medical, 22 (30.1%) traumatic and 38 (52.1%) out-of-hospital cardiac arrest (OHCA). The median PaCO2 -ETCO2 gradient was 2.0 [1.3–3.1] kPa. A PaCO2 -ETCO2 gradient of 0–1 kPa was seen for only 11 (15.1%) of total patients. The Bland-Altman agreement for all aetiologies was more than the accepted gradient of 0-1 kPa with the largest bias and widest limits of agreement seen for OHCA (–3.2 [0.3 – –6.8]). Conclusion: The magnitude of the differences between the ETCO2 and PaCO2, levels of variation and inability to predict this suggest that ETCO2 is not a suitable surrogate upon which to base ventilatory settings in conditions where pH or PaCO2 require precise control.